Advances in financial risk management corporates, intermediaries and portfolios - Batten, Jonathan A.; MacKay, Peter; Wagner, Niklas F. 1969- (Palgrave Macmillan, 2013)
"Advances in Financial Risk Management: Corporates, Intermediaries and Portfolios is essential reading to those interested in better understanding developments in the post-Global Financial Crisis (GFC) environment. There are seventeen papers that provide the latest research on measuring, managing and pricing financial risk, allocated into three very broad perspectives: risk management in non-financial corporations; in financial intermediaries such as banks, which must comply with regulatory standards on measuring and managing risk; and finally within the context of a portfolio of securities of different credit quality and marketability. This unique compilation of papers provides an expansive view of the latest techniques available to academics and practitioners to measure and manage risk"..